Mathematical Analysis of Thermophoresis and Chemical Reaction Effect on Micropolar Fluid Flow in the Presence of Nano Particles - Stepha, N. Golden; Vijayakumar, G. Nixon Samuel; Muralidharan, K. (Communications in Mathematics and Applications, 2023)
The present study focused on forced convective heat and mass transfer flow of viscous fluid in the presence of chemical reaction. A two-dimensional incompressible flow of a micropolar nanofluid past a continuously moving porous plate with variable viscosity is investigated. The viscous dissemination is considered in the energy condition. The governing boundary layer equation renovated into ODEs by considering similarity transformation. Numerical solution is obtained by adopting 4th order R-K numerical procedure together with NS shooting method. The impact of the parameters on the fluid concentration, temperature, velocity, and angular velocity are analyzed graphically for nano particle volume fraction \((0<φ<2)\). The results of the flow model for different flow factors are exactly in line with the flow's physical conditions. It is explored that the increase in nano particle volume fraction \(φ\) causes decline in both microrotation and velocity of the fluid close to the boundary and for increasing thermophoretic parameter, both species concentration and fluid temperature decreases. The fluid's velocity and rotational velocity are lower in the solution with higher density nano particles.